PKM Pendapingan Bimbingan Teknis Administrasi Keuangan Badan Usaha Milik Desa (BUMDES) Di Desa Borisallo Kecamatan Parangloe Kabupaten Gowa - Hairuddin, Sitti Hartati; Arsyad, Muhammad; Lannai, Darwis (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2024)
This PKM program will be implemented in Borisallo Village, Parangloe District, Gowa Regency which has a lot of potential natural resources. so it is important to manage village assets. The establishment of BUMDesa is intended not only to become a driving force for the wheels of the village economy but also to serve as a source of village income. For this reason, village financial management must be handled professionally. As a village financial institution that runs a financial business that meets the needs of micro-scale businesses run by village economic entrepreneurs, BUMDesa is required to make financial reports for all BUMDesa business units. every month honestly and transparently. BUMDesa is also required to provide progress reports on BUMDesa business units to village communities through village meetings at least twice a year. Therefore, it is necessary to provide financial administration technical guidance skills to the Borisallo Village Owned Enterprise (BUMDesa). The activities that will be developed in this PKM program are assistance in increasing the knowledge of Village-Owned Enterprises by conducting technical guidance on village financial administration so that BUMDesa can expand their types of business in managing Borisallo Village assets so as to increase BUMDesa income. With this PKM program, partner groups will be empowered, so they are able to access their potential. Meanwhile, the approach being developed is a learning by doing approach. From the results of this PKM activity, partners (Employees of BUMDes Borisallo) have understood the potential of village assets to be used as a source of village income and recorded simple financial management as a basis for reports to the community.